HIERARCHY OF CHARACTERISTIC TIME SCALES OF THE VARIATIONS IN THE GEOMAGNETIC FIELD - Petrova G.N. (My University, 1989)
The pattern of relationships between characteristics scales in the earth's structure discovered by M.A. Sadovskiy and analyzed in his publications pointed the way for a new line of geophysical research. An interesting aspect of scale relationships is the hierarchy of characteristic time scales in the variation of the geomagnetic field. Three main types of change in the geomagnetic field are known: secular variation, excursions, and reversals. The secular variations are stable quasiperiodic fluctuations of the geomagnetic field with characteristic time scales between 101 and 104 years and with changes in direction of up to 20°. The agreement between the estimates of the characteristic time scale calculated by two independent methods suggests that this oscillation does indeed occur. Reversals of the geomagnetic field, i.e., reversals of the direction of the earth's magnetic moment, occur at various time intervals. A first-order approximation of the distribution of reversals in the Phanerozoic has been developed, and various investigators have identified characteristic time intervals between reversals that occur through the entire Phanerozoic or in certain of its subdivisions. Excursions, the third type of change in the geomagnetic field, present the greatest difficulty in the search for a hierarchy of characteristic time scales. The unreliable dating of the six oldest excursions is somewhat compensated by the fact that the hierarchical ratios for the six more reliably dated excursions are the same as those for the scale as a whole. This consistent value of the hierarchical ratios in all types of variation of the geomagnetic field is a striking phenomenon that obviously merits careful study.